Ludwig Leichhardt's ghosts : the strange career of a traveling myth - Hurley, Andrew Wright (Studies in German literature, linguistics, and culture., 2018)
"After the renowned Prussian scientist and explorer Ludwig Leichhardt left the Australian frontier in 1848 on an expedition to cross the continent, he disappeared without a trace. Andrew Hurley's book complicates that view by undertaking an afterlife biography of 'the Humboldt of Australia.' Although Leichhardt's remains were never located, he has been sought and textually 'found' many times over, particularly in Australia and Germany. He remains a significant presence, a highly productive ghost who continues to 'haunt' culture. Leichhardt has been employed for all sorts of political purposes. In imperial Germany, he was a symbol of pure science, but also a bolster for colonialism. In the 20th century, he became a Nazi icon, a proto-socialist, the model for the protagonist of Nobel laureate Patrick White's famous novel Voss, as well as a harbinger of multiculturalism. He has also been put to use by Australian Indigenous cultures. Engaging Leichhardt's ghosts and those who have sought him yields a fascinating case study of German entanglement in British colonialism in Australia. It also shows how figures from the colonial past feature in German and Australian social memory and serve present-day purposes. In an abstract sense, this book uses Leichhardt to explore what happens when we maintain an open stance to the ghosts of the past"--